Miniature Printed Magnetic Photonic Crystal Antennas Embedded into Vehicular Platforms - Irci, Erdinc; Sertel, Kubilay; Volakis, John L. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, a miniature printed antenna utilizing magnetic photonic crystal (MPC) modes is presented. Typically, MPC modes are supported by a combination of anisotropic dielectric and ferrimagnetic layers. Here, these modes are emulated using coupled printed lines on a grounded dielectric substrate with small, biased ferrimagnetic inclusions. The resonant antenna is formed by cascading two unit cells excited with a probe feed. A recessed, cavity-backed version of this antenna is embedded into a vehicular platform with a goal to minimize platform effects. Several locations on the vehicle are studied and antenna placement is optimized using a combination of two commercially available electromagnetic simulators.